Apolipoprotein A1 and heterogeneous nuclear ribonucleoprotein E1 implicated in the regulation of embryo implantation by inhibiting lipid peroxidation. Issue 5 (November 2016) - Jia, Jia; Gou, Jinhai; Zhao, Xia; Yi, Tao; Li, Zhengyu
Abstract: It is known that apolipoprotein A1 (apoA1) is a stimulator of endothelial nitric oxide synthase (eNOS), and that heterogeneous nuclear ribonucleoprotein E1 (hnRNP-E1)-containing RNP complexes is a key protector of basal stabilization of eNOS mRNA. Recently, we found that apoA1 and hnRNP-E1 were up-regulated during peri-implantation period, and the purpose of this study was to explore the roles of apoA1 and hnRNP-E1 during this period in the mouse. It was found that the up-regulation of apoA1 and hnRNP-E1 were dependent on the presence and status of blastocysts, on endometrial decidualization and on the progesterone and 17β-oestradiol status. Knockdown of apoA1 or hnRNP-E1 both resulted in reduced numbers of embryo implantations and neonates ( P < 0.01), and lipid peroxidation was found to be involved. On pregnancy day 5 eNOS expression and superoxidase dismutase (SOD) quantity were increased, and malondialdehyde (MDA) quantity was decreased at implantation sites. The knockdown of either apoA1 or hnRNP-E1 led to down-regulation of eNOS ( P < 0.01) and to an increase in the quantity of MDA ( P < 0.05), and a decrease in the amount of SOD ( P < 0.01). These findings suggest that apoA1 and hnRNP-E1 may play roles in embryo implantation by inhibiting lipid peroxidation.